Culturally appropriate pedagogical development for classrooms with Confucian heritage values: a perspective with visual communication students - Yam, Angeline Min-Yee (2024)
Over the last decade, learning styles of Confucian-Heritage-Culture (CHC) have been widely discussed as typically passive – learners showed unwillingness to ask questions and often hesitant to speak up. It has been suggested that the collectivist nature of Confucian values such as keeping social harmony, avoidance of conflicts and having great respect for the teacher have resulted in a passive learning environment for CHC learners with high reliance on the teacher figure. Classroom activities that require active verbal interaction often results in awkward silences. This becomes a problematic issue within a design classroom setting where critique session is a common form of pedagogy used to provide opportunities for students to inquire and reflect about their design work by interacting with a community of shared interest and learning. Our paper attempts to adopt a practical inquiry into how theories of social constructivism in particularly learning via social interaction and Confucian influences can be fused and adapted for CHC visual communication students.